مؤثر اسلامی تبلیغ کے لیے مطلوبہ مہارتیں؛عصر حاضر کے تناظر میں: Essential Skills for Effective Islamic Preaching: A Contemporary Perspective - Umbreen, Dr. Faryal; Akram, Samreen; Imtiaz , Raheela (Al-Amīr Research Journal for Islamic Studies, 2024)
Prophetic guidance has emphasized the importance of equipping da’wah (Islamic preaching) with both sincerity and skill. The final Prophet ﷺ was sent as a universal messenger, leaving his followers with the responsibility to carry the message of Islam forward until the Day of Judgment. In this context, Allah SWT addresses the Ummah: "You are the best community raised up for humanity; you enjoin what is right and forbid what is wrong." Given the complexity of the modern world, successful da’wah now requires specialized knowledge and skills that are relevant to contemporary challenges. This paper seeks to explore the essential skills needed for effective da’wah in today’s world. Divided into two sections, the first part analyzes the growing need for da’wah amidst modern societal challenges. The second section delves into specific skills that are indispensable for a successful da’i (preacher), offering recommendations for skill development and effective engagement. This study aims to support da’wah efforts by providing practical insights that align with current societal contexts. Keywords: Da’wah, Islamic Preaching, Contemporary Skills, Modern Da’i, Effective Da’wah Techniques, Islamic Communication Skills